Hyper-IgE and Carcinoma in CADINS Disease - Pietzsch, Leonora; Körholz, Julia; Boschann, Felix; Sergon, Mildred; Dorjbal, Batsukh; Yee, Debra; Gilly, Vanessa; Kämmerer, Eva; Paul, Diana; Kastl, Clemens; Laass, Martin W.; Berner, Reinhard; et al. (Frontiers in Immunology, 2022)
Background Atopic dermatitis (AD) affects up to 25% of children and 10% of adults in Western countries. When severe or recurrent infections and exceedingly elevated serum IgE levels occur in AD patients, an inborn error of immunity (IEI) may be suspected. The International Union of Immunological Societies classification lists variants in different genes responsible for so-called Hyper-IgE syndromes. Diagnosing an underlying IEI may influence treatment strategies. Methods Clinical and diagnostic workup of family members are presented including a detailed immunological description and histology of the carcinoma. Functional testing of the novel variant in CARD11 underlying ‘CARD11-associated atopy with dominant interference of NF-kB signaling’ (CADINS) was performed. Results We report on an 18-year-old patient with a long-standing history of infections, accompanied by hypogammaglobulinemia, intermittent agranulocytosis, atopy, eosinophilia and colitis. The working diagnosis of common variable immunodeficiency was revised when a novel heterozygous CARD11 variant [c.223C>T; p.(Arg75Trp)] was identified. Functional studies confirmed this variant to have a dominant negative (DN) effect, as previously described in patients with CADINS. Five other family members were affected by severe atopy associated with the above variant, but not hypogammaglobulinemia. Malignancies occurred in two generations: an HPV-positive squamous cell carcinoma and a cutaneous T-cell lymphoma. So far, one patient is under treatment with dupilumab, which has shown marked benefit in controlling severe eczema. Conclusion The phenotypic spectrum associated with heterozygous CARD11 DN mutations is broad. Partial T-cell deficiency, diminished IFN-γ cytokine and increased IL-4 production, were identified as disease-causing mechanisms. Malignant disease associated with germline CARD11 DN variants has only been reported sporadically (1). HPV vaccination in teenage years, and cytology screening analogous with routine cervical swabs may be recommended. Treatment with dupilumab, a monoclonal antibody blocking interleukin-4- and interleukin-13 signaling, may be of benefit in controlling severe and extended AD for some patients as reported for STAT3 loss-of-function.